PENINGKATAN KOMPETENSI EMKM DAN BUMDES: PELATIHAN DAN PENDAMPINGAN AKUNTANSI KEUANGAN DI WILAYAH CIGANITRI, KABUPATEN BANDUNG - Koerniawan, Koenta Adji; Mahardika, Dewa Putra Krishna; Fahlevi, Ali Riza (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
The empirical fact that is currently happening is that EMKM and BUMDES entrepreneurs in the Ciganitri area do not understand what and how financial reports are presented according to standards. The implication is that they cannot give financial reports, so the financial position of the business cannot be determined accurately, as a result, the assessment of financial performance fails, and tax reporting cannot be determined precisely. Increasing competence in financial accounting through training and mentoring is an urgent solution. This activity was attended by 25 participants from various EMKM and BUMDES business units. This abdimas aims to help EMKM and BUMDES entities understand basic finance and introduce the use of the Si Apik and SIABDES accounting applications for preparing financial reports according to EMKM financial accounting standards (SAK). The methods used in Community Service include problem identification, field surveys, training, post-training assistance, and assessments, to measure the achievement of community service outcomes. The results obtained show an increase in the understanding of the Community Service participants. They are starting to be interested in applying the Si Apik accounting application or SIABDES for the purpose of presenting financial reports according to standards so that their obligations in realizing transparency and accountability can be helped to be realized.